National Museum of Qatar: New Architectural language, New Vision - Al-Hammadi, Mariam Ibrahim (Journal of History Culture and Art Research, 2020)
The original Qatar National Museum that was established in 1975 as a pioneer museum in the gulf region was closed in 2005 for renovation. The new National Museum of Qatar (NMoQ) took more than a decade, around fourteen years from 2005-2019 to accomplish. It is one of Qatar’s mega projects, which was opened with a VIP opening celebration that was held in 27th of March 2019, and opened officially for the public on 28th. After more than a decade in creation, the NMoQ finally designed to reflect and narrate the story, history and ambition of the state and to become an icon for modern Doha. Ever since its establishment in 1975 the national museum has been a matter of making a place for the Qatari culture and history. Although the museum is refurbished into totally new vision and setting, it still belongs to the same history and serves the same nation. Both visions are pursuing to identify the continuance progressions of the country, which takes the state’s history as its stem. However, we need to know which methodology the current establishment is using, and to what drama it could lead? What differences does the present introduce with respect to the past? This paper discusses and analyses the interpretation of the Qatari culture, heritage, and history, by examining the architecture of the new NMoQ. The purpose of the paper is to trace and compare the national museum’s presentation and interpretation of Qatari culture and history, between the past and present, through its architecture. In addition, the paper investigates the changing economic, social, and political codes of Qatar through the reordering of cultural materials.